NEED ASSESSMENT OF UKRAINIAN REFUGEES IN NORTH MACEDONIA (Security Dialogues, 2025)
Between mid-May and mid-June 2022, 10 students from the Faculty of Philosophy,supported by 3 Ukrainian language interpreters, conducted 49 interviews with refugees fromUkraine, overall covering 244 individuals in Skopje, Ohrid, Stip and Bitola. This report presentsthe main findings relating to refugees’ profiles, intentions, and needs, aiming to provide anevidence-based document to support advocacy interventions that will be most beneficial tothese refugees, complementary support to the one to be provided by the government as wellas individual assistance when/if needed.Key findings• The majority of refugees from Ukraine are women and children, with high levelsof education and diverse professional skills among adults• While most refugees hope to return to Ukraine one day, for the time being, themajority plan to stay in their current host country
Keywords: refugees, need assessment